Opozycja w Chinach. Wczoraj, dzis i jutro - Kaczmarek, Piotr (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The essay is about the opposition in a political system of People’s Republic of China. First of all, the most important historical changes were described. The next part of a text is connected with a present political situation in China. The rules of political system and the domination of Communist Party of China over other parties are presented. However, the examples of oppositionists’ activity seem to be the most essential. Liu Xiaobo as a symbol of fight for human rights and democracy attracted much attention. Unfortunately, the popularity of opposition movements seems to decrease. The weakness of opposition is an ally to the government. Finally, the text tries to predict the future.